Choreographies of Emotion: Sociological Stories behind Bedtime, Fairy Tales and Children's Books - Costa, Rosalina (2013)
This article casts a sociological gaze on the ordinary and seemingly unimportant daily moment of bedtime, and the bedtime practices involving parents and children. As modern-day parents often accuse themselves of being ‘under pressure’ and having ‘time scarcity’ when trying to balance work and family demands, children’s bedtime is more and more perceived as a family ritual that stops the accelerated pace of everyday life and allows for the parent–child relationship construction and enhancement. Drawing on both middle-class men’s and women’s accounts collected through qualitative episodic interviews, this article explores bedtime practices between parents and small children as arenas of emotion socialization. Findings suggest that children’s bedtime tends to be valued as an expression of child centrality in contemporary family; nonetheless, the circumstances surrounding this moment as a ‘time for emotion’ are quite different and socially constructed vis-à-vis parents’ participation in the labour market, gender dynamics and family configuration. These data unveil the ways in which children’s bedtime is indexical of those shifting family forms and the multiple contexts within which they are embedded, and at the same time they call for a deeper dialogue between psychology and sociology when trying to understand those choreographies of emotion.